Effect of solvents on polylactide fiber morphology prepared by electrospinning process - ศรีเทพ, ยศฐา; เวียงอินทร์, อรปรียา; ละม่อม, อลงกรณ์ (RMUTSB ACADEMIC JOURNAL, 2019)
Nanofibers have been used in the industries and biomedical applications for years. This research aimed to study the effect of different solvents on the morphology of polylactide (PLA) nanofibers prepared by electrospinning process. Polylactide was dissolved in difference solvents like acetone, chloroform, and dichloromethane. The ratio of polylactide and solvents was 10 and 90 by weight. The solvents used in this study were acetone, chloroform and dichloromethane. Moreover, the effects of fiber spinning using mixed solvents were studied. In which the polymer solution was spun by the electrospinning machine. The flow rate was 1 millimeter per hour, the distance between the capillary needle and the drum collector was 15 centimeter, the voltage was 15 kilovolts and the spinning time was 3 hours. The morphology and size of nanofibers were determined. The results showed that the nanofibers produced by the mixed of acetone/chloroform at the ratio of 35/65 by weight had the most consistent and the lowest average diameter of 1253.18 nanometer.